Filsafat Moral dan Islam : Ekspresi Kebahagiaan Individu Pada Jejaring Sosial Media - Fitria Husna; Ja’far Assagaf (Pusat Riset dan Inovasi Nasional, 2023)
One of the basic needs of every human being is to find happiness and be able to express it. One alternative that is often used by individuals in expressing happiness is social media. Happiness is also basically relative, depending on which perspective the expression of happiness is valued. This paper will search to describe various expressions of individual happiness on social media. The general concept of happiness from the perspective of the study of moral philosophy, in this case, hedonism and eudaimonism, is used in this paper as an analytical knife for this phenomenon. In addition, as a comparison, Islamic values are also presented in this theme. This type of study is library research with the main data sources being national journals, books, and other reading materials. The results of this study found that expressions of happiness on social media are quite diverse including shared reality, self-portraits (selfies), obtaining rewards, exploring and obtaining various entertainment from social media, and charity activities. Besides that, there are also expressions of happiness that are capable of harming others, including bullying and sharing hoaxes. These various activities have positive and negative positions from the point of view of moral philosophy and then the concept of Islam was born to complement and give birth to signs of obtaining happiness on social media.